THE INVESTIGATION OF QUESTKIONING SKILLS ACCORDING TO COGNITIVE STEPS OF RENEWED BLOOM TAXONOMY IN SOCIAL STUDIES TEACHER CANDIDATES (Third Sector Social Economic Review, 2019)
This research was carried out on Social Studies Teacher candidates in order to reveal high level questioning skills related to geography subjects. Field research method was used in the study. In this study, which was chosen as the purposive sampling method; The research data were collected in the 2018-2019 academic year from voluntary students who were attending the 4th grade Social Studies Education Program of the education faculties of a university located in Inner West Anatolia and a long-established university in Ankara . In order to collect data ""to prove scientifically that the world is round"" informative text about the subject is given.According to the text content, participants were asked to prepare 6 to 10 questions and the data were subjected to content analysis. The results of the research revealed that the participants does not have high level questioning skills. According to the findings, the distribution of the questions to the cognitive steps of Renewed Bloom Taxonomy is as follows; '' Remembering '' with 55,2 % of the most questions produced as a step, 24,4 % '' Understanding '', 14,8 % '' Analysis '', 4,6 % '' Creation '' and '' Evaluation '' 0,8 % of the step questions were asked. There was no question asked about “pratical” step. In addition, there was no significant difference between the participants' faculty and high level questioning skills.
Keywords: Renewed Bloom Taxonomy; cognitive steps; social studies teacher candidates